Pemikiran Ibnu Taimiyah Tentang Talak Tiga (Kajian Kitab Al-Fatawa Al Qubro) - Ayu, Diyan Putri; nafiah, Nafiah; Fathoni, Khoirul (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This article aims to find out how Ibn Taimiyah thought about the triple divorce in one word contained in the book al-Fatawa al-Qubra, where this opinion differs from the opinion of several other madhhab scholars, and to find out the istinbath used by Ibn Taimiyah. about triple divorce in one word. This research method uses descriptive analysis method, where the author in this case tries to describe Ibn Taimiyah's opinion about triple talaq at once by using primary data sources, namely the book of al-Fatawa al-Kubra by Ibn Taimiyah. From these problems, it can be analyzed that Ibn Taymiyya argued that in dropping three divorces one time, the divorce law only fell one divorce. This opinion is stronger than the opinion of the Imam Madzhab scholars who say that three divorces are punishable by three divorces. Because Ibn Taimiyah's opinion is considered more authentic, the hadiths used are less mafsadah due to the divorce compared to the opinion of the Imam Madzhab scholars. Thus, the arguments used by Imam Madzhab scholars are considered weak by Ibn Taimiyah and his group, some are mujmal due to ambiguity. So according to Ibn Taimiyah, the arguments used by Imam Madzhab scholars are not appropriate to be used as reasons for the law of divorce in three words